ENCODING THE IMAGE OF THE MOON ON NGUYEN DU'S THE TALE OF KIEU - Trần Thị Bảo Giang (Tạp chí Khoa học Đại học Đà Lạt)
In “The Tale of Kieu” by Nguyen Du, the moon appears 63 times throughout the story and has many meanings. This article is based on the point of view of semiotics to encode the different meanings of the moon in “The Tale of Kieu”, such as: Code 1 – the peaceful moon; Code 2 – the transformation of the moon; Code 3 – the moon and the movement of time. Therefore, the moon in this story gradually becomes an autonomous system of signs with a life of its own.